On trauma and traumatic memory - Majoul, Bootheina (Cambridge Scholars Publishing, 2017)
On Trauma and Traumatic Memory focuses on the role of writing to preserve memories, to excavate traumas and to heal the ever-present scars of the past. The first part of the book focuses on trauma recalled through films, fiction and documentaries. The second chapter is devoted to analysing trauma in fiction, while the third deals with trauma in poetry. The topic of trauma is of interest to scholars across the globe, both students and professors, and is taught in almost all universities. This volume gathers research papers from different universities around the world, including the India, Italy.